Concurrent effect of supra-threshold TENS applied over tibialis anterior muscle decreases mediolateral sway of healthy young adults - Vidovič, Marko; Kafel, Tibor; Šuc, Lea; Rugelj, Darja; Weber, Daša (Frontiers in Physiology, 2025)
IntroductionPostural stability during quiet standing relies on effective sensorimotor integration. Sensory stimulation techniques, commonly applied to the lower limbs, have been used to enhance sensory input and reduce postural sway. This study investigated the immediate effects of transcutaneous electrical nerve stimulation (TENS) applied over the tibialis anterior (TA) and triceps surae (TS) muscles on postural sway in healthy young adults. A secondary aim was to compare the postural responses between the two stimulation sites.MethodsTwenty healthy volunteers (28.1 ± 3.8 years) participated in this study. Supra-threshold TENS at 100 Hz was applied over the TA and TS muscles in two separate sessions. Four postural sway variables were analyzed in the time domain: center of pressure (CoP) velocity, mediolateral and anteroposterior path lengths, and sway area. Testing was performed under both eyes-open and eyes-closed conditions.ResultsTENS applied over the TA muscle significantly decreased mediolateral sway path length under eyes-closed conditions. No significant effects were observed for stimulation over the TS muscle, nor for either site under eyes-open conditions.DiscussionThese findings suggest that supra-threshold TENS at 100 Hz applied over the TA muscle may improve postural stability in more demanding sensory conditions (i.e., eyes closed), with effects specifically observed in the mediolateral direction. No significant impact of TS stimulation was found under either visual condition. Further research is warranted to investigate the effects of prolonged or repeated TENS application and its potential to enhance postural control.